STUDY ON MECHANICAL CHARACTERISTICS OF RECYCLED CONSTANT VELOCITY DRIVESHAFT FOR SANTNA AUTOMOBILE - ZUO Li; LU Xi (Jixie qiangdu, 2015)
Using constant velocity universal drive shaft of Santana Automobile with different service lives,mechanical characteristics such as natural frequency and hardness were investigated. The results show that natural frequency of drive shaft decreases slightly with the increase of service life. The maximum of reduction for natural frequency is1. 2%. The high-rank natural frequency decreases more obviously than the low-rank,but no regulation was found. Surface hardness of different cross-sections changes slightly,which shows a trend from rise to decline. According to the changes of natural frequency and hardness,it predicts that drive shafts have over 60% service life.